Factors Associated With Uptake Of Post-Abortion Family Planning Among Women Of Reproductive Age Seeking Postabortion Care In Nyeri County Referral Hospital - Mulah, Joseph; Mbuthia, Florence (Journal of Midwifery and Nursing, 2024)
Globally, > 75 million Women of Reproductive Age (WRA) needs Post Abortion Family Planning (PAFP) yearly after treatment of pregnancy loss. However, results from several studies show that majority of these women fail to access PAFP as needed. Efforts made to support uptake of PAFP in Sub-Saharan African (SSA) has borne little success and the uptake of PAFP remains crucially low. This study assessed factors associated with uptake of PAFP among WRA seeking PAC in Nyeri County Referral Hospital (NCRH). A descriptive cross-sectional study was used. The study population was WRA seeking PAFP as a component of PAC after having a pregnancy loss. The study sample included WRA who sought PAC at gynecological ward in NCRH during the time of study from February 11th 2023 to March 20th 2023. A researcher-administered questionnaire was used. Quantitative data was managed using SPSS version 25.  The rate of uptake of PAFP was 56.4%. Factors associated with the uptake of PAFP were: sociodemographic factors that included age, marital status, education level, occupation and parity. Health system related factors included: healthcare provider attitudes.